2016
DOI: 10.17957/ijab/15.0135
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Study of Interactive Effect of Cadmium and Salicylic Acid on Growth and Biochemical Parameters in Tetra and Hexaploid Wheat

Abstract: In vitro cultures of plants offer a useful tool to study the adaptive mechanisms of plants in the presence of high metal concentrations. Callus cultures of tetraploid (Durum-97) and hexaploid (Shafaq-06) wheat genotypes exposed to different cadmium (Cd) concentrations (0, 100, 400, 800 and 1200 µM) and its alleviation by salicylic acid (0, 0.5 mM) were assayed for growth, antioxidant responses and Cd accumulation characters. Cadmium hampered the growth and notably enhanced antioxidant activity in all Cd regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Salicylic acid has been known to be phytotoxic to many crops when used at high concentrations. Enhancing effects of exogenous SA application on plant growth have been reported in several crops (Gharib 2006;Gawade and Sirohi 2011;Khandaker et al 2011). Therefore, our findings can add cassava to the list of such crops.…”
Section: Discussionsupporting
confidence: 66%
“…Salicylic acid has been known to be phytotoxic to many crops when used at high concentrations. Enhancing effects of exogenous SA application on plant growth have been reported in several crops (Gharib 2006;Gawade and Sirohi 2011;Khandaker et al 2011). Therefore, our findings can add cassava to the list of such crops.…”
Section: Discussionsupporting
confidence: 66%
“…Likewise, it was found that the callus cultures of two wheat genotypes, tetraploid (Durum-97) and hexaploid (Shafaq-06), which were under Cd toxicity, raised Cd accumulation in the callus with the augmentation of Cd doses in the medium. The usage of 0.5 mM SA led to decreased BCF value to less than 1 in higher concentrations of Cd 68 . Similarly, seed priming of Linum usitatissimum L. with SA reduced the amount of Cd in the root and shoot of this plant, and as a result, the values of BCF, BAC, and TF were reduced to less than one.…”
Section: Resultsmentioning
confidence: 89%
“…Researchers Ghani (2010), found that with increasing cadmium, the length of root, stem and total plant decreased and the decrease in the root length of plants was greater than their stems [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%